Efficacy Of Acceptance And Commitment Therapy For Emotional Distress In The Elderly With Type 2 Diabetes: A Randomized Controlled Trial - Maghsoudi Z; Razavi Z; Razavi M; Javadi M (Diabetes, Metabolic Syndrome and Obesity, 2019)
Zahra Maghsoudi,1 Zohreh Razavi,2 Mohammadreza Razavi,1 Mostafa Javadi3 1Student Research Committee, Hamadan University of Medical Sciences, Hamadan, Iran; 2Saman Psychology Clinic, Yazd, Iran; 3Research Centre for Nursing and Midwifery Care, Shahid Sadoughi University of Medical Sciences, Yazd, IranCorrespondence: Mostafa JavadiNursing Department, Nursing and Midwifery School, Safaieh, Yazd, IranTel +98 8 13 827 1145Email mostafajavadi1880@gmail.comIntroduction: Diabetes is among the common diseases in the elderly which results in depression, anxiety, and emotional distress in the elderly and impacts the disease control by the individual. This study was conducted with the aim of exploring the effectiveness of acceptance and commitment therapy (ACT) in the improvement of emotional distress in the elderly with type 2 diabetes.Materials and methods: In this randomized control trial, 80 elderly with type 2 diabetes aged ≥60 years were randomly selected among the individuals visiting Yazd Diabetes Research Center. Then, the patients were randomly divided into two 40 individual groups, ie, the intervention group and the control group. The intervention group underwent group ACT during eight 90-min sessions. The diabetes-related emotional distress questionnaire was completed before the intervention, after the end of the group sessions and 2 months after that. The statistical software SPSS version 21 was used for data analysis.Results: The emotional mean scores in the intervention and control groups were not significantly different before the intervention. However, the mean score of the intervention group was lower than of the control group immediately after the intervention (p=0.02) and 2 months after the intervention (p=0.02).Conclusion: ACT results in the improvement of diabetes-related emotional distress in the intervention group. Considering the effectiveness of ACT, this therapeutic method is recommended to be used for the amelioration of emotional distress in the elderly with type 2 diabetes.Keywords: acceptance and commitment therapy, emotional distress, elderly